Epidemiology of Leishmania Carriers in Tan Chang County, Gansu Province, China - Han, Shuai; Chen, Sheng-bang; Yang, Zhang-hong; Feng, Yu; Wu, Wei-ping (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Leishmaniasis is a regional infectious disease caused by the bite of Leishmania-carrying sandflies. The clinical symptoms include prolonged fever, spleen enlargement, anemia, emaciation, leukopenia, and increased serum globulin levels. If not appropriately treated, patients may die of complications caused by leishmaniasis within 1–2 years after the onset of the illness. Therefore, further investigation of the mechanisms of infection by this pathogen is required. Here, an epidemiological study of Leishmania carriers was conducted. The potential mechanism of infection through domestic animals as carriers of the parasite was investigated to identify potential reservoir hosts for Leishmania. Methods: The rK-39 strip test was performed on blood samples from previously infected patients. Blood samples were collected from the patients and their families. The blood, liver, spleen, and diaphragm muscle samples were collected from livestock. To perform nested polymerase chain reaction (PCR), DNA was extracted and the internal transcribed spacer sequence was used. The amplified products were then subjected to restriction fragment length polymorphism and phylogenetic analyses. Results: Among previously infected patients, 40% (12/30) showed positive results in the rK-39 strip test. The nested PCR positive rates for previously infected patients/relatives and livestock samples were 86% (77/90) and 80% (8/10), respectively. Moreover, the phylogenetic analysis showed that the pathogen was Leishmania infantum. Dogs, patients, and domesticated animals carrying Leishmania were found to be a potential source of infection for leishmaniasis. Conclusions: The results of this study provide a basis for developing disease prevention and control strategies for leishmaniasis.